First records of the cremastocheiline genus Clinterocera Motschulsky, 1858 from the Indonesian island of Sulawesi, with description of a new species (Coleoptera: Scarabaeidae: Cetoniinae) - Krikken, J. (Zootaxa, 2016)
A new species of the myrmecophilous Asian genus Clinterocera Motschulsky, 1858 (Coleoptera: Scarabaeidae: Cetoniinae: Cremastocheilini) is recorded from three localities on different parts of Sulawesi island (Indonesia). These are the first published records of the genus from the island. The taxonomic position and ecology of Clinterocera are briefly discussed. The male holotype of Clinterocera heinrichi new species comes from Central Sulawesi while a second male specimen from North Sulawesi male seems different enough to be placed in another species-group taxon, but more material needs to be examined first.